Self-reported workplace perception as indicators of work anxieties. (28th October 2015) - Muschalla, B.; Fay, D.; Linden, M.
Abstract : Background: Work anxiety is a potentially disabling mental health problem, which can cause (long-term) sickness absence. In many cases patients do not openly report their anxieties and tend to give externalizing explanations of inner problems. Therefore people with work anxiety may perceive their workplace more negatively than those without such anxiety. Aims: To investigate the relation between subjective work description and work anxiety. Methods: Work anxiety was investigated with a standardized interview in a sample of employed psychosomatic rehabilitation inpatients suffering from common mental disorders. We assessed their subjective perception and evaluation of workplace conditions with the 'Short Questionnaire for Job Analysis' (KFZA) and compared their results with those from a sample of employees in the general population. Results: There were 148 inpatient participants and 8015 general population controls. Patients with work anxiety described their workplace significantly more negatively than patients without work anxiety and employees in the general population, with no differences in workplace descriptions between psychosomatic patients without work anxiety and the general population sample. The type of complaint about work conditions was related to the specific type of work anxiety. Conclusions: Reports about workplace burdens can be indicative of work anxiety and should prompt further in-depth assessments. The content of complaints about work conditions may point to the type of underlying work anxiety.